Molecular Detection and Phylogenetic Analysis of Canine Distemper Virus in Marsican Brown Bear (Ursus arctos marsicanus) - Cristina Esmeralda Di Francesco; Camilla Smoglica; Vincenza Di Pirro; Federica Cafini; Leonardo Gentile; Fulvio Marsilio (Animals, 2022)
In this paper, we report the first molecular detection of the canine distemper virus in the Marsican brown bear (Ursus arctos marsicanus). Three subadults and one adult were live-trapped and checked for the main viral pathogens responsible for infectious diseases in this species. The four bears were found to be negative for all investigated viruses except for one, which resulted in a positive outcome for CDV by means of RT-PCR targeting fragments of viral N and H genes. The sequence analysis revealed the specificity of amplicons for the Europe Wildlife lineage of CDV, the same viral strain recovered from three foxes and two unvaccinated dogs coming from the same territories where the positive bear was captured. These results confirm the receptivity of Marsican brown bear for CDV, apparently without any pathological consequences for the positive animal, and suggest the presence in the studied area of a unique wild host-adapted lineage of the virus, able to spread in domestic animals, too. In this respect, continuous and specifically targeted surveillance systems are necessary in order to highlight any changes in the epidemiology of the infection in the territories where the Marsican brown bear lives, along with a more effective vaccination program for domestic dogs co-existing with this endangered species.